Performance Assessment of Public Service Agency in Implementing the Public Housing for Low Income Society Program in Indonesia’s Provinces - ra afera ratna wijayanti (IULI Publisher, 2023)
Abstract. Indonesia's population continues to grow and spread throughout the islands in Indonesia. Along with the increase in population, what is important is the availability of decent housing for residents who have low incomes. This prompted the government to create a special housing availability program for productive people with low incomes per month. In order to achieve the success of implementing this program, it is necessary to carry out research as well as surveys on the construction sites of housing units spread across all provinces in Indonesia, where this research was taken from 11 provinces, involving housing development companies, banks and the community itself. The study used the index number measurement method for compliance assessment, using primary data taken directly and conducting direct interviews with people who already own these houses in 11 provinces in Indonesia. The elements or variables under review include three elements, namely the assessment of the compliance of housing developers as companies that carry out housing construction, the compliance of banking institutions as distributors of funds to the public to be able to take homeownership loans, and compliance with the community as the party that will own the house. The point of this research focuses on the performance of Public Service Agency in terms of the Bank's compliance variable with LIC (Low Income Community) and vice versa, the LIC (Low Income Community) variable with respect to the Developer and vice versa and the Developer variable with the Bank and vice versa.The compliance assessment will provide information about how successfully this program has been implemented and also how the Public Service Agency (PSA) is performing in implementing it. Keywords: Developer Complience, Bank Complience, Low Income Community Compliance, Performance